2013
DOI: 10.1016/j.niox.2013.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Simvastatin treatment increases nitrite levels in obese women: Modulation by T−786C polymorphism of eNOS

Abstract: Our results demonstrated a restoration of nitrite levels in obese women treated with simvastatin, which is modulated by T(-786)C polymorphism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…The increased NO in the present study with simvastatin treatment in congruence with several studies reported that statins improve NO bioavailability (Ozuyaman et al, 2008;Harisa et al, 2012;Li and Forstermann, 2013;Glutkina, 2013;Andrade et al, 2013). Moreover, it has been established that atheroprotective effect of statins is mediated by restoring the normal NO/peroxynitrite balance (Heeba et al, 2009).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The increased NO in the present study with simvastatin treatment in congruence with several studies reported that statins improve NO bioavailability (Ozuyaman et al, 2008;Harisa et al, 2012;Li and Forstermann, 2013;Glutkina, 2013;Andrade et al, 2013). Moreover, it has been established that atheroprotective effect of statins is mediated by restoring the normal NO/peroxynitrite balance (Heeba et al, 2009).…”
Section: Discussionsupporting
confidence: 90%
“…NO is a major player in the regulation of the cardiovascular system and reduced NO bioavailability has been linked to cardiovascular disorders (Andrade et al, 2013). The decrease of NO bioavailability associated with erythrocyte dysfunction and cardiovascular complications (Mason et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Multiple agents within these broad classes of medication have been shown to upregulate endothelial (e) NOS activity [42][43][44]. When the current cohort was split for drug classifications, no differences in baseline plasma nitrite were detectable.…”
Section: Placebomentioning
confidence: 99%
“…The CC genotype was also associated with reduction of plasma sCD40-L, sVCAM, sP-selectin and MMP-9 in response to atorvastatin, in health men (Souza-Costa et al, 2007). NOS3 -786C allele was also associated with the increase in blood nitrite but not with the reduction of plasma malondialdehyde in obese women treated with simvastatin (Andrade et al, 2013).…”
Section: Endothelial Function-related Genesmentioning
confidence: 87%